A responsabilidade social no processo de adoção de inovação em empresas sucroenergéticas do centro-oeste do Estado de São Paulo. - Lampkowski, Francisco José [UNESP]; Biaggioni, Marco Antônio Martin [UNESP]; Lampkowski, Marcelo (My University, 2013)
The main objective of this paper was to verify the influence of the organization and management in social responsibility the decision of adoption, choice, justification and implementation of innovation in elaborates of sugar, ethanol and energy companies of the midwestern state of São Paulo. Using multivariable analysis of principal components and clusters, the variables were analyzed and companies classified. Adapted to contemporary situations, the Freeman (1975) model of taxonomies was the parameter with research information in personal interviews by semi-structured questionnaires. The activities investigated were the existence of programs and organization to improve the welfare and quality of life to employees and family (leisure, culture, health, self-knowledge, values, beliefs etc.), program and social volunteering organization for the community, programs and organization to encourage the training of educators and extension education and incentive programs and organization to research and scientific production. It was concluded that the best companies which included, in their organization structures, management practices embodied in social responsibility.

O objetivo principal deste trabalho foi verificar a organização e influência da gestão em responsabilidade social na decisão de adoção, escolha, justificativa e implementação de inovação praticadas nas empresas sucroenergéticas do centro-oeste do Estado de São Paulo. Utilizando-se de análise multivariada de componentes principais e de agrupamentos, as variáveis foram analisadas e as empresas classificadas. Adaptado às situações contemporâneas, o modelo de taxionomias de Freeman (1975) foi o parâmetro com informações pesquisadas em entrevistas diretas por questionários semi-estruturados. As atividades investigadas foram: a existência de programas e organização para melhorias do bem-estar e qualidade de vida dos funcionários e familiares (lazer, cultura, saúde, autoconhecimento, valores, crenças, etc.), programas e organização para o voluntariado social comunitário, programas e organização para o incentivo à formação de educadores e extensão de ensino e programas e organização para o incentivo a pesquisa e produção científica. Conclui-se que as melhores empresas com posturas inovadoras são aquelas que em suas estruturas de organização, incorporam as práticas da gestão em responsabilidade social.
Keywords: Innovation; Technology; Social responsibility; Sugar, ethanol and energy companies.; Inovação; Tecnologia; Responsabilidade Social; Empresas sucroenergéticas.